Rationalizability, cost-rationalizability, and Afriat's efficiency index - Matthew Polisson; John K.-H. Quah (Institute for Fiscal Studies (IFS), 2022)
This note explains the equivalence between approximate rationalizability and approximate cost-rationalizability within the context of consumer demand. In connection with these results, we interpret Afriat's (1973) critical cost efficiency index (CCEI) as a measure of cost (in)efficiency, in the sense that a consumer is spending more money than is required to achieve her utility targets.
Keywords: D11; D12; 330; rationalizability; cost-rationalizability; Afriat's efficiency index; CCEI